Peningkatan Motivasi Belajar Siswa Dalam Pembelajaran IPS Menggunakan Metode Pembelajaran Quantum Teaching Learning Kelas IV SD Negeri 66 Kota Ternate - Rachmatia Tauhid (Peneliti.net, 2023)
The background of this research is the low learning motivation of fourth grade students at SD Negeri 66 Kota Ternate. The research aims to find out (1) how to increase social studies learning motivation using the Quantum teaching learning method; (2) can the use of the Quantum teaching learning method increase motivation in social studies subjects as a whole in class IV A students at SD Negeri 66 Kota Ternate in the 2022/2023 academic year. This type of research is Classroom Action Research. The subjects of this study were 25 students in class IV of SD Negeri 66 Kota Ternate in the 2022/2023 academic year. The object of this research is to increase students' learning motivation in social studies subject. The instruments used in this study were questionnaires, motivational observation sheets. The data analysis technique used is descriptive quantitative and qualitative analysis. The results showed that: (1) efforts to increase social studies motivation and achievement using the Quantum Teaching Learning method can be carried out with the Quantum Teaching Learning learning design, namely grow, experience, name, demonstrate, repeat, celebrate; (2) the application of the Quantum Teaching Learning method can increase motivation. This can be seen from the initial condition of the student motivation score of 52.55 (very less) the number of students who have a minimum good motivation is 3 students with a percentage of 12%. After the action was taken in cycle I it increased to 78.11 (good) then with the action in cycle II it increased to 87.15 (very good) the number of students who had a minimum good motivation was 25 students with a percentage of 100%; so that it can be concluded that the use of the Quantum teaching learning method can increase learning motivation in social studies learning in class IV SD Negeri 66 Kota Ternate.